80. Local field potential recording abnormalities precede deep brain stimulation surgical complications in a patient with Parkinson's disease. Issue 1 (January 2015) - Rosa, M.; Arlotti, M.; Cortese, F.; Cogiamanian, F.; Ardolino, G.; Rampini, P.; Carrabba, G.; Locatelli, M.; Levi, V.; Priori, A.
<x xml:space="preserve">Abstract</x> Local field potentials (LFP) are oscillatory bioelectrical signals arising from large neuronal populations around an electrode inserted into the central nervous system. LFP recorded through deep brain stimulation (DBS) electrodes have been mainly used for experimental purposes. We report the case of a 72-year-old woman with Parkinson's disease, who had electrodes implanted bilaterally into the subthalamic nucleus (STN) for DBS. The patient underwent bilateral STN LFP recordings two and seven days after surgery. Three days after surgery a slight weakness developed in the left limbs and a CT scan disclosed a small hemorrhagic area localized caudal to the electrode tip, in the right midbrain. Before DBS-related complications became clinically and neuroradiologically evident LFP recordings, in comparison to the contralateral side, disclosed a markedly reduced amplitude and the absence of the typical spectral peak in the right STN. This report describing STN LFP abnormalities preceding the clinical and neuroradiological evidence of a focal brain lesion suggests that recording oscillatory biopotentials through DBS electrodes could also be useful in clinical practice. This case report is unusual and novel because none have reported LFP changes associated with a brain lesion or suggesting a DBS-related complication.